THE IMPORTANCE OF POLYMORPHISMS OF REGULATORY AND CATALYTIC ANTIOXIDANT PROTEINS IN CHRONIC KIDNEY DISEASE - Jerotic, Djurdja (Medicinski podmladak, 2021)
Both excessive production of reactive oxygen species (ROS) and impaired antioxidant function are found in patients with chronic kidney disease (CKD). Therefore, individual susceptibility towards CKD can be induced by functional variations of genes encoding antioxidant regulatory (nuclear factor erythroid 2–related factor 2 (Nrf2)) and catalytic (superoxide dismutase (SOD2) and glutathione peroxidase (GPX1)) proteins. Several types of single nucleotide polymorphisms (SNPs) have been found within the genes encoding these proteins, with Nrf2(-617C/A), SOD2(Ala16Val) and GPX1(Pro198Leu) conferring impaired catalytic activity. The most unexplored gene polymorphism in CKD susceptibility, progression and survival, with only two original studies published, is the Nrf2(-617C/A) polymorphism. The results of these studies showed that there was no individual impact of this polymorphism on the susceptibility towards end stage renal disease (ESRD) development, oxidative phenotype and mortality. However, Nrf2 had a significant role in ESRD risk and survival when combined with other antioxidant genes. The results regarding the impact of SOD2(Ala16Val) and GPX1(Pro198Leu) polymorphisms on either CKD or ESRD are still inconclusive. Namely, some studies showed that patients having variant SOD2(Val) or GPX1(Leu) allele were at increased risk of CKD development and progression, while other studies reported only weak or no association between these polymorphisms and CKD. Surprisingly, the only study that reported an association of GPX1 polymorphism on overall/cardiovascular survival in ESRD patients showed a significant impact of low activity GPX1(Leu/Leu) genotype on better survival. In this review, we comprehensively and critically appraise the literature on these polymorphisms related to oxidative stress in CKD patients in order to identify gaps and provide recommendations for further clinical research and translation. New developments in the field of antioxidant polymorphisms in CKD patients could lead to better stratification of CKD patients based on a prognostic antioxidant gene panel and provide a more personalised medicine approach for the need of antioxidant therapy in these patients.
Keywords: CKD, Nrf2, SOD2, GPX1, gene polymorphisms